Peran Orientasi Kewirausahaan dan Orientasi Pembelajaran untuk Meningkatkan Kinerja UMKM - Suyatmi Suyatmi; Reza Widhar Pahlevi (Esensi: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the effect of entrepreneurial orientation and learning orientation on competitive advantage; determine the effect of entrepreneurial orientation and learning orientation on performance and determine the effect of competitive advantage on performance. The data collection method was obtained by using a questionnaire on MSME actors in the Special Region of Yogyakarta and collected 204 respondents. The data analysis tool uses the AMOS Structural Equation Modeling (SEM) technique. The results show that there is an influence between entrepreneurial orientations and learning orientation on competitive advantage, there is an influence between entrepreneurial orientation and competitive advantage on performance. However, there is no effect between learning orientation on performance